Joint association of sleep quality and physical activity with hypertension: a cross-sectional population study in agricultural workers - Chen, Yu-Fei; Zhao, Qian; Hamulati, Xieyire; Cai, Liting; Qiu, Xinyu; Maimaitiyiming, Jiamule; Liu, Fen; Li, Xiao-Mei; Yang, Yi-Ning (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThe study explores the prevalence of hypertension and evaluates the joint association of sleep quality and physical activity (PA) levels in influencing hypertension among the Kazakh agricultural workers in Xinjiang.MethodsIn this chronic disease study conducted in Xinjiang, participants were selected from Habahe County, a predominantly Kazakh region, between October and November 2023. Restricted cubic spline (RCS) analysis and multivariate logistic regression models were used to evaluate the associations between sleep quality, PA levels, and the prevalence of hypertension.ResultsIn this study of 2,872 participants, the median age was 49 (42–57) years. Among participants, 1,253 (43.63%) were male. The study resulting in a hypertension prevalence of 54.94%. RCS regression showed a linear association between sleep quality and hypertension prevalence in participants (P overall = 0.007, P nonlinear = 0.214), and the association between PA level and hypertension prevalence was also statistically significant (P overall = 0.022). As PA level increased, hypertension prevalence gradually declined but stabilized at higher level. In a multivariate regression analysis adjusting for potential confounders, poorer sleep quality was associated with an increased prevalence of hypertension (OR = 1.33, 95% CI: 1.07–1.65, P = 0.011; OR = 1.38, 95% CI: 1.12–1.69, P = 0.001), while the association between PA level and hypertension prevalence was not statistically significant (P > 0.05). Further analysis showed that in the moderate PA level group, good sleep quality was significantly associated with a lower prevalence of hypertension (OR = 0.71, 95% CI: 0.52–0.97, P = 0.031). However, in individuals with low (<6,000 METs × min/week) and high (>12,000 METs × min/week) PA levels, the association between sleep quality and hypertension prevalence was not been observed (P > 0.05).ConclusionThe current study showed that PA and sleep quality are associated with the prevalence of hypertension. Among individuals with moderate PA level, healthy sleep quality may have a protective effect against hypertension.